Axiological parameter of the image of a literary character - Ludmila V. Paloyko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In this article the literary text is considered from the point of view of several common humanitarian sciences such as philosophy, psychology, literature and linguistics. This synergetic approach is due to the exceptional versatility of a work of fiction as an aesthetic phenomenon and cultural heritage. One of the main functions of a literary text is its evaluation or axiological function which is primarily realized in the image of a character that performs in the text as media of ideals, norms and imperatives of an individual. In this article axiological parameter of the image of a literary character is considered by the example of Scarlett O'Hara, the heroine of the novel "Gone with the Wind" by M. Mitchell and its official sequel - "Scarlett" by A. Ripley.